عقد الإعتماد الإيجاري كوسيلة لتمويل الاستثمار في التشريع الجزائري: دراسة نظرية وتطبيقية من منظور قانوني اقتصادي - نابتي، عبدالحق يوسف Nabeti, Abdulhaq Yousuf (المركز الجامعي عبد الحفيظ بوالصوف ميلة, 2019)
تعد صعوبات تمويل المشاريع الاقتصادية عن طريق الاقتراض المصرفي، أهم الدوافع التي ساهمت في بروز تقنية الاعتماد الإيجاري كأسلوب تمويلي أخذ يتنوع بعد ظهوره استجابة لتنوع الحاجات التمويلية للمؤسسة الاقتصادية، حيث عرفت ازدهارا معتبرا لما لها من أهمية في تخطي صعوبات التمويل المصرفي، المتمثل أساساً في مشكلة تباطء إجراءات الحصول على القرض، والضمانات لقاء ذلك، والتمويل الجزئي للمشاريع. اعتمدت هذه التقنية كوسيلة لتمويل الاستثمار في الجزائر سنة 1996 بموجب الأمر 96- 90، حيث سمحت قواعده بتوفير مزايا تنافسية بالمقارنة مع وسائل التمويل الأخرى لأطراف العلاقة من مستأجرين ومؤجرين وموردين، وما رافقه من أثر إيجابي في التنمية المستدامة للاقتصاد الوطني ككل. حاولنا من خلال هذا البحث دراسة مدى فعالية ونجاعة التشريع الجزائري لأداء تقنية الاعتماد الإيجاري دورها بالفعالية والكفاءة المرجوة منها.
The difficulties of financing economic projects through bank borrowing are the most important factors that led to the emergence of leasing as a financing method, which varies after it appears in response to the diversification of the financial needs of the economic institution. Leasing has seen considerable prosperity because of its importance in overcoming the most important difficulties of bank financing; which is mainly the problem of slow procedures for obtaining the loan, and guarantees for this, and partial funding. This technique was adopted as a means of financing investment in Algeria in 1996 under Ordinance No. 96 - 90 on rental dependence. Its rules allowed competitive advantages in comparison to other financing means of tenants, lessors and suppliers, and their impact on the Sustainable development of the national economy as a whole. In this study, we tried to study the effectiveness and efficiency of Algerian legislation for the performance of the leasing system in its effective and efficient role.
Keywords: تمويل الاستثمارات -- القوانين والتشريعات -- عقود الإيجار -- الجزائر